If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -3 = -3x + -3x + 1 Reorder the terms: -3 + -2x = -3x + -3x + 1 Reorder the terms: -3 + -2x = 1 + -3x + -3x Combine like terms: -3x + -3x = -6x -3 + -2x = 1 + -6x Solving -3 + -2x = 1 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -3 + -2x + 6x = 1 + -6x + 6x Combine like terms: -2x + 6x = 4x -3 + 4x = 1 + -6x + 6x Combine like terms: -6x + 6x = 0 -3 + 4x = 1 + 0 -3 + 4x = 1 Add '3' to each side of the equation. -3 + 3 + 4x = 1 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = 1 + 3 4x = 1 + 3 Combine like terms: 1 + 3 = 4 4x = 4 Divide each side by '4'. x = 1 Simplifying x = 1
| 3/10-1/6= | | 5x+3(x+6)=74 | | 2y^2-4y^3=0 | | .4(a+3)=2 | | -14-3x=16+2x | | 14=3s-4b | | x+5-5=17-5 | | log(6+x)+log(6-x)-logx=2 | | 4m^2+8m+32=0 | | 18-n/2 | | 11=3x-25 | | 10x+4x+3+6=8x+3+5x | | 12y^2+7y+10=0 | | 19x=23x+38 | | 500-11N=170 | | 3v/4=12 | | 2x+2x-14=x-9+x+2+x-7 | | -48x^5/6x | | 4.9t^2-10t+84=0 | | 5t+3=5(t+25)-22 | | (a+2)(a-5)(a+3)= | | 5t-4=44-t | | 3x^4/12x^2 | | -1/3y-4-7 | | Radx+5-radx-1=2 | | 9z+15=8z+12 | | Sinxcosy=7x^2 | | 5x+10=8x+10 | | 15=8-(z+10) | | 42/4a=4 | | 3m-2/3=211/3 | | 6x-1=11+5 |